The effects of an educational intervention based on the protection motivation theory on the protective behaviors of emergency ward nurses against occupational hazards: a quasi-experimental study - Mohadeseh Nouri; Saeed Ghasemi; Sahar Dabaghi; Parvin Sarbakhsh (BMC, 2024)
Abstract Background Emergency ward nurses face a variety of occupational hazards due to the nature of their occupational and professional duties, which can negatively affect their health. Therefore, this study aimed to evaluate the effects of an educational intervention based on the protection motivation theory on the protective behaviors of emergency ward nurses against occupational hazards in Tehran, Iran, in 2023. Methods The present quasi-experimental study was conducted with two intervention and control groups, using a pretest-posttest design. A total of 124 nurses working in the emergency wards of four hospitals (two hospitals for the intervention group and two hospitals for the control group by random assignment) were selected by multistage sampling method. The educational intervention based on the protection motivation theory was implemented for the intervention group for three weeks. The nurses of both groups completed a demographic questionnaire and the scale of emergency ward nurses' protective behaviors against occupational hazards before, immediately, and one month after the intervention. Data analysis was performed using descriptive and inferential methods. Results The two groups were similar in terms of demographic characteristics at the baseline (p > 0.05). Protective behaviors of emergency nurses against occupational hazards and their sub-scales (physical, chemical, biological, ergonomics, and psychosocial hazards) were higher in the intervention group than in the control group immediately and one month after the educational intervention. In addition, the measurement over time also showed the positive effect of time and educational intervention on the protective behaviors of emergency nurses against occupational hazards and their sub-scales in the intervention group. Conclusion These findings showed that the educational intervention based on the protection motivation theory can be effective and helpful in improving the protective behaviors of emergency ward nurses against occupational hazards and their sub-scales. Future studies can focus on a more specific design of this kind of intervention based on the type of occupational hazards and needs of nurses in different wards.